KESANTUNAN BERBAHASA TINDAK TUTUR IMPERATIF PADA ACARA INI TALK SHOW DI NET TV - Siti Aisah (Jurnal Bahasa Lingua Scientia, 2020)
The research was distributed by speakers often use the speech act the imperative of using imperative is not directly on the show Talk Show on NET TV. This research was conducted to describe, first, the principle of politeness on the show is a Talk Show, and second; describe the shape of the speech act event is imperative on a Talk Show. This type of research is a qualitative descriptive method. This research instrument is its own researchers assisted with books relating to the research. This research data taken with video how to download this show Talk Show from Youtube Edition January 2016. Based on the results of the study can be summed up as the following things. First, the principle of politeness that is found in the speech act event is imperative on a Talk Show is the tact maxim , generosity maxim, agreement maxim, sympathy maxim. Second, the imperative form of the shareholder said on a Talk Show this event is imperative reigning speech act, telling, asking, pleading, urgent, cajoling, appealed, inviting, call request, permission, permit, prohibition, expectations, and advice.